Tension-Band Wiring For Transverse Fractures of the Patella, Olecranon and Medial Malleolus: A Prospective Single-Centre Study - Dr.Vinay B Patil; Dr Eshwar Masgal; Dr Vijayakumar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Transverse fractures of the patella, olecranon and medial malleolus threaten joint mechanics and daily function. Tension-band wiring (TBW) converts distracting tensile forces into compression and permits early motion, but contemporary prospective data across the three sites are sparse. Methods Fifty skeletally mature patients with acute, closed transverse fractures (patella 25, olecranon 20, and medial malleolus 5) were enrolled at a tertiary trauma unit (May 2023 – Oct 2024). All fractures were stabilised with AO-standard TBW and followed for 18 months. Functional outcomes were assessed serially with Gaur’s Knee Score, Mayo Elbow Performance Score (MEPS) or the AOFAS Ankle-Hind-foot Scale. Union was graded radiographically. Complications and re-operations were recorded. Results Mean age was 38 ± 14 years; 56 % were male. Union was achieved in 48/50 fractures (96 %) with a median time to radiological union of 11 weeks (IQR 10–13) (Figure 2). At 18 months, 88 % of knees demonstrated excellent–good knee-ROM scores, 91 % of elbows scored ≥ 75 on MEPS, and 80 % of ankles scored ≥ 90 on the AOFAS scale (Table 2-4; Figure 1). Quadriceps wasting, power loss and extension lag all improved steadily over each review point. Complications included two painless wire breakages and two non-unions (one patella, one olecranon) managed by revision plating; there were no deep infections or implant migrations. Conclusion TBW provided reliable union, high functional scores and a low complication burden across three anatomically distinct peri-articular fracture sites. Its simplicity, cost-effectiveness and allowance for early mobilisation make it a valuable primary fixation method, particularly in resource-constrained settings.